2019
DOI: 10.1111/jocs.14261
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected intraoperative obstruction of frozen elephant trunk in patients who underwent total arch replacement

Abstract: Currently, total arch replacement (TAR) using frozen elephant trunk (FET) technique is gaining popularity for various thoracic aortic pathologies. FROZENIX is the first commercialized open stent-graft (OSG) in Japan, and it is a useful alternative to previously self-made OSG. FROZENIX is easy to deploy compared with formerly launched OSGs. However, some challenges have been identified with FROZENIX.Herein, we present the cases of two patients in whom we encountered serious unexpected kinking of FROZENIX during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Incidence of graft kinking with the Frozenix HP was more variable, and overall, the highest, which represents a great concern over the safety and effectiveness of this FET graft. Uchida et al ( 13 ) reported 2 cases of TAR with FET using the Frozenix J Open Graft, both of whom developed stent graft kinking which was related to the stent graft's structural property ( 13 ). Here, during the first case, specifically, after the Frozenix HP was inserted into the downstream aorta and its distal anastomosis completed, high cardiopulmonary bypass (CPB) flow-line pressure (300 mm Hg) and low femoral arterial pressure were noted, suggesting FET graft obstruction.…”
Section: Incidencementioning
confidence: 99%
See 4 more Smart Citations
“…Incidence of graft kinking with the Frozenix HP was more variable, and overall, the highest, which represents a great concern over the safety and effectiveness of this FET graft. Uchida et al ( 13 ) reported 2 cases of TAR with FET using the Frozenix J Open Graft, both of whom developed stent graft kinking which was related to the stent graft's structural property ( 13 ). Here, during the first case, specifically, after the Frozenix HP was inserted into the downstream aorta and its distal anastomosis completed, high cardiopulmonary bypass (CPB) flow-line pressure (300 mm Hg) and low femoral arterial pressure were noted, suggesting FET graft obstruction.…”
Section: Incidencementioning
confidence: 99%
“…Other reported cases of kinking identified intraoperatively were treated by pulling out of the non-stent part of the graft proximally and then re-anastomosing the distal part into a distal site. Uchida et al ( 13 ) described performing this technique on a patient in Japan where the Frozenix stent graft was initially used. Similarly, for another patient, the same authors described taking out the Frozenix graft, trimming it, and re-anastomosing the graft more distally ( 13 ).…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations